ANALISIS PEMASANGAN VARIASI SUDUT VORTEX GENERATOR BERKONFIGURASI COUNTER-ROTATING PADA AIRFOIL NACA 2412 - Adiwidya Ega Fadila (2021)
Drag and separation on the airfoil is a detrimental component. To overcome this, flow control is needed, one of which is a Vortex Generator (VG). This research was conducted with the aim of knowing the effect of airfoil performance that has been added with VG with variations in the VG installation angle. The results of the airfoil simulation on the CFD application are also seen. This research was conducted with 2412 airfoil with Re 1.5 x 105 and then installed VG with variations in angles of 10o, 20o, and 30o. This research was conducted with CFD application. In terms of performance, the airfoil installed with VG has a lower Lift Coefficient (CL) value than the airfoil without VG. At the value of the Drag Coefficient (CD) all airfoils installed with VG have a larger CD than airfoils without VG, the higher the angle of installation of the VG installed, the larger the CD. The flow velocity in the middle between a pair of VGs shows that the separation that occurs will decrease as the installation angle of VG increases. However, if between 2 pairs of VG, the separation will increase as the installation angle of VG increases. For the pressure created, when VG is installed, the pressure created increases when the VG installation angle increases.